MOBILE-BASED APPLICATIONS DETERMINATION OF NETWORK COMPUTER TECHNIQUES FOR VOCATIONAL COMPETENCE TESTS OF VOCATIONAL SCHOOL OF PRINGSEWU DISTRICT - Erma Dwiyani; Siti Mukodimah (IJISCS (International Journal of Information System and Computer Science), 2019)
Quality Vocational High Schools are viewed from the feasibility of facilities and infrastructure that help develop students' skills in the learning process so that they can meet the standards of Vocational Competency Test. The purpose of this study is to find out the quality of the Computer Network Engineering laboratory facilities owned in Pringsewu Regency. In this study five alternatives were used as samples to be tested for the feasibility of the Network Computer Engineering laboratory to determine the quality of the laboratory owned by the Vocational High School related to using the calculation process manually and the process of calculating using the system. The due diligence process uses the system faster with accurate results compared to the manual calculation process which takes a long time. Based on the comparison of the due diligence process, it can be said that the due diligence process uses a faster, more precise and easier system.